2017
DOI: 10.1097/aud.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Sound Localization and Speech Perception in Noise of Pediatric Cochlear Implant Recipients: Bimodal Fitting Versus Bilateral Cochlear Implants

Abstract: Overall, the binaural performance was similar to each other between children who are fit with two CIs (CI + CI) and those who use bimodal stimulation (HA + CI) in most conditions. However, the bilateral CI group showed better speech perception than the bimodal CI group when babble was from the first device side (first CI side for bilateral CI users or CI side for bimodal listeners). Therefore, if bimodal performance is significantly below the mean bilateral CI performance on speech perception in babble, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…4,26 The central auditory system can selectively suppress the impact of noise and improve speech perception when there is binaural hearing input from different directions. This phenomenon is called the binaural squelch effect, 19 whereas binaural summation is the integration of the acoustic signal by the central auditory system, improving the perceptual loudness of the acoustic signal when hearing binaurally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,26 The central auditory system can selectively suppress the impact of noise and improve speech perception when there is binaural hearing input from different directions. This phenomenon is called the binaural squelch effect, 19 whereas binaural summation is the integration of the acoustic signal by the central auditory system, improving the perceptual loudness of the acoustic signal when hearing binaurally.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, binaural benefits could be related to the duration of auditory deprivation, asymmetrical degeneration in binaural neural pathways and maturation of binaural temporal processing in the auditory cortex. 19 Wieringen et al discussed the neural processing of adults and children and highlighted that children's brains were highly sensitive to the loss of auditory input and that the growth and development of the cerebral cortex among these patients are diverse according to the varying degrees of congenital and acquired unilateral deafness as a result of imbalanced auditory input. 2 The results of the present study further demonstrated the short-and long-term performance of Bonebridge implantation in patients with single-sided deafness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bimodal localization abilities are highly variable with conflicting reports regarding bimodal benefit. Specifically, some studies have demonstrated significant bimodal benefit for horizontal plane localization (e.g., Choi et al, 2017;Potts et al, 2014) and other studies have shown little-tono benefit over unilateral hearing alone (e.g., Dorman et al, 2016;Potts & Litovsky, 2014).…”
Section: Bimodal Hearing Versus Bilateral Cochlear Implantsmentioning
confidence: 99%
“…[20][21][22]. Но ряд объективных (отсутствие источников финансирования) и субъективных (отказ пациента или родителей от проведения еще одного хирургического вмешательства) факторов проводит к тому, что пациент с глухотой имеет только один кохлеарный имплант [20,[23][24][25].…”
Section: Introductionunclassified